Treatment Patterns for Metastatic Urothelial Carcinoma Across Eight Mexican Centers: The ALEBRIJE Study - Evelyn Lilian Beas-Lozano; Yuly A. Remolina-Bonilla; Rosa Caballero; Nora Sobrevilla-Moreno; Perla Perez-Perez; Maria Guadalupe Díaz-Alvarado; Omar Alejandro Zayas-Villanueva; Erika Adriana Martinez-Castañeda; Saul Campos-Gomez; Luis Arturo Cardoso-Aparicio; Dolores Mendoza-Oliva; Maria T. Bourlon (JCO Global Oncology)
PURPOSEMetastatic urothelial carcinoma (mUC) poses a challenge to health care systems, given its treatment complexity and mortality. We aimed to describe the characteristics, treatment patterns, and survival outcomes of Mexican patients with mUC.METHODSA retrospective study was conducted across eight centers for adults with mUC from January /2001 to December 2021. We recorded medical history, eligibility for first-line platinum therapy, treatment lines received, and access to novel drugs. Descriptive statistics were used and survival analysis, including Kaplan-Meier curves and Cox proportional hazards model, was performed.RESULTSWe identified 379 patients with mUC; 37 were excluded, and 76% was male, with a median age of 67 years. The median follow-up was 8.4 months. Among those who received a first-line treatment (65%), cisplatin-based chemotherapy (45%) was the most common followed by carboplatin (39%). Causes of cisplatin ineligibility were Eastern Cooperative Oncology Group ≥2 (41%) and glomerular filtration rate <60 mL/min (33%). The overall response rate to up-front platinum therapy was 33%, with a median progression-free survival of 6.1 months (95% CI, 4.9 to 6.9). Second-, third-, and fourth-line treatment was given to 24.6%, 8.8%, and 3.5%, respectively. Chemotherapy was the most common regimen prescribed. Access to novel drugs was limited, 14 patients received avelumab, and 25% received immunotherapy as second-line treatment. The median overall survival was 11.8 months (95% CI, 10.2 to 15.2). Multivariate analysis showed that first-line treatment was independently associated with better survival, whereas poor performance status and visceral disease were associated with worse survival.CONCLUSIONTo our knowledge, these data represent the first effort to delineate treatment trends of mUC in Mexico. First-line treatment prescription and rates of progression to platinum therapy were higher than those described worldwide. Factors affecting survival included performance status, first-line treatment, and visceral disease. Our study highlights unequal access to novel treatments, underscoring the need for equitable care.